2017
DOI: 10.1016/j.bpj.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Study Reveals How Receptor and Ras Synergistically Activate PI3Kα and PIP3 Signaling

Abstract: Cellular pathways controlling chemotaxis, growth, survival, and oncogenesis are activated by receptor tyrosine kinases and small G-proteins of the Ras superfamily that stimulate specific isoforms of phosphatidylinositol-3-kinase (PI3K). These PI3K lipid kinases phosphorylate the constitutive lipid phosphatidylinositol-4,5-bisphosphate (PIP2) to produce the signaling lipid phosphatidylinositol-3,4,5-trisphosphate (PIP3). Progress has been made in understanding direct, moderate PI3K activation by receptors. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 42 publications
12
46
0
Order By: Relevance
“…To determine if either p110α or p110δ bound to Q572* represented a fully activated form we tested the activation by lipidated HRas, which activates p110α and p110δ through increased membrane recruitment. We found that lipidated HRas activated both p110α and p110δ bound to Q572* similar to the activation seen with wildtype p85α ( Fig 1E) (Buckles et al, 2017;Siempelkamp et al, 2017).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…To determine if either p110α or p110δ bound to Q572* represented a fully activated form we tested the activation by lipidated HRas, which activates p110α and p110δ through increased membrane recruitment. We found that lipidated HRas activated both p110α and p110δ bound to Q572* similar to the activation seen with wildtype p85α ( Fig 1E) (Buckles et al, 2017;Siempelkamp et al, 2017).…”
Section: Resultssupporting
confidence: 76%
“…This is consistent with previous results showing that the combination of the activating point mutation in the C2 domain of p110α and the Q572* truncation does not lead to additive activation ). However, the complex of Q572* with p110α does not represent a fully activated form, as kinase activity can still be stimulated by the presence of lipidated HRas similar to wild type p110α/p85α (Buckles et al, 2017;Siempelkamp et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K isoforms are differentially activated downstream of Ras superfamily members ( 39 , 41 ), with p110α and p110δ being activated downstream of Ras family GTPases, and p110β being activated downstream of Rho family GTPases. Ras activates PI3K through enhanced membrane interaction, with Ras activation being strongly synergistic with activation downstream of phosphorylated receptors ( 42 , 43 ). Mutant p110α deficient in its ability to be activated by Ras leads to decreased oncogenic transformation, tumor maintenance, and angiogenesis downstream of mutant Ras ( 44 46 ).…”
Section: Signaling Inputsmentioning
confidence: 99%
“…The central substrate is a product of P13K, i.e. phosphatidylinositol 3,4,5 triphosphate (PIP3) [26]. Cyclins and Bcl-2 proteins correlate closely with cell cycles and apoptosis, respectively [27].…”
Section: Discussionmentioning
confidence: 99%